2004
DOI: 10.1007/s11199-004-5466-4
|View full text |Cite
|
Sign up to set email alerts
|

On Versus Off the Pitch: The Transiency of Body Satisfaction Among Female Rugby Players, Cricketers, and Netballers

Abstract: In this study I investigated the development of body satisfaction among women rugby players, cricketers, and netballers. I also sought to assess the impact of sport participation on both athletic and "feminine" identity. Semistructured interviews were conducted with 10 rugby players, 10 cricketers, and 10 netballers. The interviews focused on the experience of playing sport and the impact sport had made on respondents' perceptions of their bodies. Using Interpretative Phenomenological Analysis to explore the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 54 publications
8
42
2
2
Order By: Relevance
“…In addition, different sports types were also not significantly associated with differences in girls' appearance satisfaction, contrary to previous research that found variable associations with body satisfaction (Smolak et al, 2000). Conflicting body ideals have previously been reported by female sports participants, particularly as they move between the sporting and social contexts (Krane, Michelnok, & Stiles-Shipley, 2001;Russell, 2004).…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 93%
See 2 more Smart Citations
“…In addition, different sports types were also not significantly associated with differences in girls' appearance satisfaction, contrary to previous research that found variable associations with body satisfaction (Smolak et al, 2000). Conflicting body ideals have previously been reported by female sports participants, particularly as they move between the sporting and social contexts (Krane, Michelnok, & Stiles-Shipley, 2001;Russell, 2004).…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 93%
“…Functional and Aesthetic Body Image 23 physical skill (Russell, 2004). Although functional body image in the current study was more pronounced for girls participating in sports and physical activity, our results also illustrated that sports and physical activity participation were associated with higher valuation of the body's attractiveness and higher investment in the body's appearance, particularly when sports were aesthetically focused.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 41%
See 1 more Smart Citation
“…However, BID usually leads people to start a physical activity program, Oliveira [14] emphasizes, since a well-planned exercise routine can reduce body weight and make them reach bodies that they idealize. In this line, Russel [15] states that some studies have shown that women who practice physical activity have a more positive perception of their body.…”
Section: Discussionmentioning
confidence: 99%
“…The construction of femininity and athleticism, specifically in TMS, is exceptionally problematic for adolescent females as they are at a particularly vulnerable age in relation to body image, self-esteem, physical appearance and pressure to conform to gender ideologies (Bowker, Gadbois & Cornock, 2003;Russell, 2004). Self-esteem, self-efficacy and body image are related strongly to whether females feel they are conforming to their gender roles as based on gender role expectations (Horn, Newton & Evers, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%